DUKUNGAN KELUARGA DALAM MENGHADAPI KECEMASAN MENOPAUSE PADA WANITA USIA 40-50 TAHUN : LITERATUR REVIEW - Ria Riana Permata Dewi; Iswandari, Novita Dewi (Midwifery And Complementary Care, 2022)
Background: Menopause is a condition where a woman no longer experiences menstruation that occurs in the age range of 50 to 58 years. At this time it is very complex for women because they will experience changes in physical health that will affect their psychological health. Therefore, menopausal women need the support of their husbands and families in carrying out their daily activities so as to create feelings of happiness, feel cared for and can reduce anxiety. Research conducted by (Septiani, 2019) from 11 countries in Latin America states that postmenopausal women experience anxiety disorders (61.9%), physical change disorders that affect quality of life (13.7%), urogenital (25.5%), psychological (18.5%), and somatic (4.5%). Objective: This study aims to analyze family support in dealing with anxiety in women aged 40-50 years. Methods: This study uses a literature review study approach using indexed data bases such as Google Scholar, e-Resource National Library of Indonesia. Results: From 10 journals of family support in dealing with anxiety in menopause, it was found that there were 3 journals about poor knowledge, this is due to the influence between knowledge and anxiety experienced by respondents because respondents already have standard knowledge. 2 journals about low education this is due to the fact that the mother's education level is one of the factors that will affect the level of maternal anxiety about menopause and 4 journals with good family support because husband's support is needed by women who will enter menopause, because at this time This time a woman has started to show a decreased physiological function of the body. Conclusion: From 10 literature review journals, it was concluded that there was an effect of the relationship of family support in dealing with menopausal anxiety in women aged 40-50 years. Keywords: Family Support, Anxiety, Menopause